Evaluation of the Quality of Transportation Services in Trans Semanggi Suroboyo with the Support of the Gobis Application System - Rahny Clarissa Pudja Irvania; Sri Kamariyah; Zaenal Fatah (International Journal of Humanities and Social Sciences Reviews, 2026)
This study aims to evaluate the quality of Trans Semanggi Suroboyo public transportation services with the support of the GoBis application system as a form of digital-based public service innovation in the city of Surabaya. The research method used is qualitative descriptive with the SERVQUAL (tangible, reliability, responsiveness, assurance, empathy) theoretical approach. The data used includes secondary data from the Surabaya Transportation Office, with the number of GoBis users reaching 327,018 people, GoBis balance users 42,833 people, and saving ticket users 2,095 people. The results of the study show that the tangible and reliability dimensions are relatively good, shown through modern fleet conditions and fairly consistent departure schedules. However, in the dimensions of responsiveness, assurance, and empathy, there are still obstacles related to the speed of response of digital systems, transaction security, and limitations of users' digital literacy. The utilization of GoBis' digital transaction feature is still low compared to the total number of application users. This study concludes that the success of Trans Semanggi Suroboyo is highly dependent on the integration between the quality of physical services and the effectiveness of the digital system. It is necessary to strengthen technological infrastructure, improve data security, and digital education for the public so that the quality of smart transportation in the city of Surabaya can run optimally and sustainably according to the principles of smart mobility.